Experimental Study and Exergy Analysis About the Flat Plate Solar Collector - Kareem , Fadhil Abdulrazzaq; Skheal , Osamah Raad; Lafta, Noor Samir (International Journal of Integrated Engineering, 2022)
The experimental study of the Flat Plate Solar Collector (FPSC) had been done during the three daysâ€™ time (2,3 and 4 of June). It is also, that the testing time was from 09:00Am up to 03:00Pm in order to give more obvious data. Energy and Exergy analysis equations had utilized to study the 1st and 2nd law of thermodynamics and to provide more appropriate results about the performance of the FPSC. The conducted results showed an enhancement in the FPSC efficiency with respect to the increase of the solar irradiance where the last one was explained through one day time. Furthermore, the FBSC exergy and energy efficiencies had the same behaviors during the daytime due to the effect of the solar radiation.  In addition, the useful exergy and the exergy efficiency are rise with the progression of time until it reaches approximately midday and then dropped because the temperature and radiation begin to decrease and its values â€‹â€‹increase with the increase in the flow rate.